Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Given:
[tex]\[ u = \binom{3}{-2}, \quad v = \binom{-12}{5} \][/tex]

(a) Find [tex]\[ u - 2v \][/tex].


Sagot :

Sure, let's solve the problem step-by-step.

You are given two vectors [tex]\( u \)[/tex] and [tex]\( v \)[/tex]:

[tex]\[ u = \begin{pmatrix} 3 \\ -2 \end{pmatrix} \][/tex]
[tex]\[ v = \begin{pmatrix} -12 \\ 5 \end{pmatrix} \][/tex]

We need to find [tex]\( u - 2v \)[/tex].

Step 1: Compute [tex]\( 2v \)[/tex].

First, multiply the vector [tex]\( v \)[/tex] by 2:

[tex]\[ 2v = 2 \cdot \begin{pmatrix} -12 \\ 5 \end{pmatrix} = \begin{pmatrix} 2 \cdot -12 \\ 2 \cdot 5 \end{pmatrix} = \begin{pmatrix} -24 \\ 10 \end{pmatrix} \][/tex]

Step 2: Compute [tex]\( u - 2v \)[/tex].

Now, subtract [tex]\( 2v \)[/tex] from [tex]\( u \)[/tex]:

[tex]\[ u - 2v = \begin{pmatrix} 3 \\ -2 \end{pmatrix} - \begin{pmatrix} -24 \\ 10 \end{pmatrix} \][/tex]

Subtract the corresponding components of the vectors:
[tex]\[ u - 2v = \begin{pmatrix} 3 - (-24) \\ -2 - 10 \end{pmatrix} = \begin{pmatrix} 3 + 24 \\ -2 - 10 \end{pmatrix} = \begin{pmatrix} 27 \\ -12 \end{pmatrix} \][/tex]

So, the result is:

[tex]\[ u - 2v = \begin{pmatrix} 27 \\ -12 \end{pmatrix} \][/tex]

Thus, the vector [tex]\( u - 2v \)[/tex] is:

[tex]\[ \begin{pmatrix} 27 \\ -12 \end{pmatrix} \][/tex]